2021
DOI: 10.1101/2021.08.12.21261943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of school closures on adolescent health-related outcomes during the COVID-19 pandemic: A natural experiment in South Korea

Abstract: A large number of countries implemented school closure as a response to the COVID-19 pandemic in 2020. As existing studies mostly rely on retrospective or pre/post comparisons that are prone to unmeasured confounding, the effect of school closure on adolescent health is poorly understood. The South Korean government implemented school closure to prevent the spread of COVID-19. A difference-in-differences comparing changes in health-related outcomes between provinces with differing degrees of school closure was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have reported that female were more mentally affected by the pandemic [ 26 , 27 ]; this worsened after the outbreak [ 28 , 29 ]. The lives of parents with school children were significantly impacted regardless of their employment status [ 30 , 31 ]. Schools were either closing or adopting an everyother-day strategy, and minimizing contact between students.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that female were more mentally affected by the pandemic [ 26 , 27 ]; this worsened after the outbreak [ 28 , 29 ]. The lives of parents with school children were significantly impacted regardless of their employment status [ 30 , 31 ]. Schools were either closing or adopting an everyother-day strategy, and minimizing contact between students.…”
Section: Introductionmentioning
confidence: 99%
“…This might be because the change in physical activity during the COVID-19 outbreak was more pronounced in boys, considering the differences in behavioral characteristics according to sex. A Korean study reported that physical activity was reduced in boys but remained constant in girls during the COVID-19 outbreak [38]. In girls, diastolic BP increased during the COVID-19 outbreak without a change in the prevalence of diastolic hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Not only does school closure prevent boys from gathering for a group activity, but also social distancing strictly restricts the use of gyms. 1 Given that physical activities among boys are largely group-based, 2 the pandemic may have limited boys’ physical activity to a larger extent. This may, in turn, have a greater impact on boys’ sitting time than girls’ sitting time.…”
Section: Discussionmentioning
confidence: 99%